2022
DOI: 10.1002/ece3.9078
|View full text |Cite
|
Sign up to set email alerts
|

Weak population genetic structure in Eurasian spruce bark beetle over large regional scales in Sweden

Abstract: The Eurasian spruce bark beetle, Ips typographus , is a major pest, capable of killing spruce forests during large population outbreaks. Recorded dispersal distances of individual beetles are typically within hundreds of meters or a few kilometers. However, the connectivity between populations at larger distances and longer time spans and how this is affected by the habitat is less studied, despite its importance for understanding at which distances local outbreaks may spread. Previous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…The data suggests high levels of connectivity among populations and a very recent differentiation into two genetic clusters (Stauffer et al 1999; Sallé et al 2007; Bertheau et al 2013; Mayer et al 2015). More recent RADseq data confirms a very weak genetic structure in the spruce bark beetle across much of Sweden (Ellerstrand et al 2022), as is expected in a species with high dispersal (Nilssen 1984) and/or recent divergence. Tajima’s D values indicate different demographic history of southern and northern group (e.g., recent expansion of southern populations and bottleneck in northern populations, Figure S7).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The data suggests high levels of connectivity among populations and a very recent differentiation into two genetic clusters (Stauffer et al 1999; Sallé et al 2007; Bertheau et al 2013; Mayer et al 2015). More recent RADseq data confirms a very weak genetic structure in the spruce bark beetle across much of Sweden (Ellerstrand et al 2022), as is expected in a species with high dispersal (Nilssen 1984) and/or recent divergence. Tajima’s D values indicate different demographic history of southern and northern group (e.g., recent expansion of southern populations and bottleneck in northern populations, Figure S7).…”
Section: Resultsmentioning
confidence: 70%
“…The data suggests high levels of connectivity among spruce bark beetle populations and a very recent differentiation into two genetic clusters [38][39][40][41] . More recent RADseq data confirms a very weak genetic structure in the spruce bark beetle across much of Sweden 42 , as is expected in a species with high dispersal 43 and recent divergence.…”
Section: Genome-wide Variation and Its Geographic Structuringcollinea...mentioning
confidence: 58%
“…A pattern of IBD was also observed among the collections of the northwestern alpine genetic cluster when the South Tyrolean cluster was excluded for analysis (Figure S4b ). Studies on Coleoptera species with great dispersal capacity have shown a weak pattern of isolation by distance, such as in Ips typographus along a transect with a diameter of 300 km in Sweden (Ellerstrand et al, 2022 ), in Ootheca mutabilis along a transect of 300 kilometres in Uganda (Kanyesigye et al, 2022 ), or in Cerotoma trifurcata along a transect of 1545 km in the USA (Tiroesele et al, 2014 ). However, the results of the present study indicate, even though genetic distance values across collections were low, that geographic distance had an effect on the genomic structure of M. melolontha , along a transect of 398 km.…”
Section: Discussionmentioning
confidence: 99%
“…These beetles may originate from the clear-cut (overwintering beetles), but also from other stands further away (dispersing beetles flying over the clear-cut by chance). Ips typographus has good dispersal capacities ( Valeria et al, 2016 ; Ellerstrand et al, 2022 ; Müller et al, 2022 ) and many specimens from foreign forest stands are likely to be attracted by pheromone traps when transiting by the experimental patches ( Weslien & Lindelöw, 1989 ). It is also possible that sanitation felling is so effective to reduce the new attacks that adding traps makes little difference.…”
Section: Discussionmentioning
confidence: 99%